LOUW, Eli van der Merwe Inventory of documents - LOUW, Eli van der Merwe. (ARCA, 2018)
Private papers of E. van der M. Louw, National Party MP Namakwaland [1977-1992]; Deputy Minister of Finance [1982-1984]; Minister of Transport [1986-1989]; Manpower [1989-1992].
COVERAGE 0,20 Metre.
Keywords: LOUW, Eli van der Merwe; Inventories; Politicians; National Party